The aesthetic discourse of glass painting skills among students of the Institute of Popular Heritage - Asst. Prof Ronak Abbood Jaber Al Mohammed (Peerian Journals Publishing, 2025)
The artist has embraced the art of painting as a pliant medium through which to convey his artistic eloquence, employing the material both as a foundation and a surface for execution— most notably in glass painting. The embodiment of aesthetic visual language manifests as a value worthy of consideration within the realm of elevated expression, particularly through the presence of skilled performance. Based on these premises, the study aimed to explore the aesthetic discourse embedded in the visual skills of glass painting among students of the Institute of Folk Heritage.
Keywords: employing; value; premises; elevated